2014
DOI: 10.1590/1516-3180.2013.7860023
|View full text |Cite
|
Sign up to set email alerts
|

Package leaflets of the most consumed medicines in Portugal: safety and regulatory compliance issues. A descriptive study

Abstract: CONTEXT AND OBJECTIVES: Package leaflets are necessary for safe use of medicines. The aims of the present study were: 1) to assess the compliance between the content of the package leaflets and the specifications of the pharmaceutical regulations; and 2) to identify potential safety issues for patients. DESIGN AND SETTING: Qualitative descriptive study, involving all the package leaflets of branded medicines from the three most consumed therapeutic groups in Portugal, analyzed in the Department of Pharmacoepid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The package leaflets that were tested were randomized using the MS Excel software function from a large database used in a previous study (with approximately 500 Portuguese package leaflets). 14 A total of 12 randomized package leaflets were tested: six package leaflets from over-the-counter medicines (three package leaflets comprising more than 1500 words and another three with less than 1500 words) and six package leaflets from prescription medicines (also with either more than or less than 1500 words). The cutoff of 1500 words was defined because previous studies had concluded that package leaflets with fewer than 1500 words tended to be easily read and understood.…”
Section: Methodsmentioning
confidence: 99%
“…The package leaflets that were tested were randomized using the MS Excel software function from a large database used in a previous study (with approximately 500 Portuguese package leaflets). 14 A total of 12 randomized package leaflets were tested: six package leaflets from over-the-counter medicines (three package leaflets comprising more than 1500 words and another three with less than 1500 words) and six package leaflets from prescription medicines (also with either more than or less than 1500 words). The cutoff of 1500 words was defined because previous studies had concluded that package leaflets with fewer than 1500 words tended to be easily read and understood.…”
Section: Methodsmentioning
confidence: 99%
“…PIs of medicinal products are very important in transmitting information on the effective and safe use of medicines [1][2][3][4]. Currently, there is a wide range of regulations worldwide concerning the adequate development and approval of PIs by marketing authorization holders and medicine agencies [5][6][7].…”
Section: Dear Editormentioning
confidence: 99%